Quasi Judicial Ombudsman: Measuring Legal Certainty After Constitutional Court Decision No. 62/PUU-VIII/2010 - Akhmadi Yasid; Slamet Suhartono; Moh. Zeinudin (Green Social: International Journal of Law and Civil Affairs, 2025)
This study discusses the legal reconstruction of the authority of the Ombudsman of the Republic of Indonesia (ORI) after the Constitutional Court (MK) Decision Number 62/PUU-VIII/2010, with a focus on advocacy based on pseudo/quasi principles. The Ombudsman, as an independent state institution, plays a role in supervising the implementation of public services to prevent and deal with maladministration. However, the existence of Article 43 of Law Number 37 of 2008 concerning the Ombudsman and the Constitutional Court's decision creates the potential for norm inharmonization that has an impact on the implementation of the Ombudsman's duties. This study analyzes two main things: legal certainty on the authority of the Ombudsman after the Constitutional Court's decision and legal reconstruction to strengthen the supervisory function of public services. The results show that the pseudo/quasi principle allows the Ombudsman to carry out an advocacy function similar to the judiciary, but without full executive power such as the judiciary. Legal certainty is needed to ensure that the Ombudsman's actions remain within the limits of the authority regulated by law. Legal reconstruction is suggested to provide stronger legitimacy to the Ombudsman's authority, including strengthening the recommendation aspect to be more binding and implementive. This reconstruction also includes increasing institutional capacity, coordination between agencies, and strengthening regulations that support supervisory functions that are more responsive to the needs of the community. Thus, this research contributes to the development of public service law, especially related to the role of the Ombudsman in realizing transparent, accountable, and fair services.